Revolutionary Writings : Reflections on the Revolution in France and the First Letter on a Regicide Peace - Burke, Edmund, 1729-1797 (Cambridge texts in the history of political thought, 2014)
"Burke's Reflections on the Revolution in France was the first sustained theoretical critique of the French Revolution; and is now recognised as the classic statement of modern conservatism. Reflections surveys the British political culture of traditionalism, gradualism and deference, and contrasts it with the French Revolutionaries' programme of appeal to abstract right, transformational change and popular agency. Ultimately Burke advocated a counterrevolutionary war and the restoration of the French monarchy. This accessible new edition brings together for the first time Burke's first and last published thoughts on the revolution including as it does the first Letter on a Regicide Peace; a work that has contributed to a particular view of international society. Featuring a comprehensive introduction and extensive annotations, Iain Hampsher-Monk's edition helps readers new to Burke to better understand the historical, political and philosophical context behind his writings, and the significance of contemporary and classical allusions"--